The mediating role of emotional exhaustion and job satisfaction on the relationship between job demands and instigated workplace incivility - Koon, Vui Yee*; Pun, Pui Yi (Sage, 2018)
High job demands are considered a risk factor for uncivil behavior in the workplace but the mechanism behind this relationship remains unclear. The current study aimed to analyze emotional exhaustion and job satisfaction as sequential mediators of the relationship between job demands and instigated workplace incivility within the integrative framework of affective events theory and the job demand–control model. Data were collected from 102 university academic staff in Klang Valley, Malaysia, via snowball sampling method. The results supported the predicted three-path mediation model with age, gender, and employment contract type as covariates. High job demands led to emotional exhaustion, which, in turn, led to a decrease in job satisfaction level and as a result gave rise to instigated workplace incivility. Implications, limitations of these findings, and directions for future research are further discussed on how to enhance and establish a civil and respectful workplace.